PENGARUH PANDEMI COVID-19 TERHADAP PERGERAKAN INCOMING DAN OUTGOING CARGO DOMESTIK DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Alprisda Windi Permatasiwi; Abdul Mu’ti Sazali; Dewi Ratnasari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The Covid-19 pandemic has an impact on several aspects of life, one of the biggest impacts on the world of aviation. Due to Pembatasan Sosial Berskala Besar (PSBB) policy that has been established by the government, passenger traffic in 2020 has decreased compared to 2019. In addition to a decrease in passengers, the Covid-19 pandemic also has an impact on the demand for air cargo. This study aims to determine the condition of cargo movement in & out during the pandemic so that it can be used as a comparison and evaluation as well as to find out the development of air cargo before the pandemic to the time of the pandemic that occurred until the start of improvement in better conditions. This research was conducted using a qualitative descriptive method using data collection techniques in the form of observation, literature study, and interviews. The results showed several factors that caused the demand for air cargo to decrease by almost 50%, which made the movement of incoming and outgoing cargo unstable. This has an impact on the occurrence of changes in the type of commodity of the cargo goods. In addition, after the Covid-19 pandemic, the mechanism for handling incoming and outgoing cargo must be paid more attention. In addition, health protocols must be implemented for the safety of cargo goods to the cargo handling personnel. However, based on the author's research, there are still frequent negligence of cargo personnel at Zainuddin Abdul Madjid International Airport Lombok in implementing health protocols.